Optimization of Access Point Placement on the Telkom Akses Wi-Fi Network Using NetSpot - ABDUR ROHMAN SYARIF; RAHMAD NOVRIANDA DASMEN (Jurnal Jaringan Komputer dan Keamanan, 2024)
The internet has become one of the most essential communication services that is widely utilized across all sectors of society. At the Telkom Akses Warehouse, Wi-Fi technology is used to provide internet connectivity for employees, technicians, and visitors. However, one of the major problems identified is that the placement of access points has been carried out solely based on immediate needs and the subjective preferences of installers, resulting in suboptimal signal distribution and unstable internet connectivity. This study aims to optimize the placement of access points on the Telkom Akses Wi-Fi network using the Action Research method and the NetSpot application as the primary analytical tool. Action Research was applied as a structured and controlled research approach to deliberately introduce changes in the network environment and monitor their impact. The results of signal level and coverage measurements indicate that the number and placement of access points required to adequately cover an area depend on the type and specifications of the access points used. After optimization, the measured signal levels reached âˆ’38 dBm to âˆ’40 dBm, which fall into the very good category. The findings further demonstrate that distance is not the only factor influencing the quality of the received signal. The physical structure of the warehouse, including walls, glass partitions, and other obstacles, also significantly affects Wi-Fi signal propagation and quality.